An exploratory study to evaluate the food waste practices of Pick n Pay - Ngwenya, Andile (The IIE, 2021)
The aim of this exploratory qualitative study was to determine if the food waste practices of Pick n Pay contributed to Pick n Pay being considered as a meaningful brand and healthy brand. Despite a number of academic literature articles focusing on food waste management and the prevention food waste in restaurants, retailers, along the supply chain and the food waste of consumers, there was no literature available focusing on food waste strategies as a contributor to meaningful and healthy brand. Food waste has become a global issue that necessitates extensive research, particularly from the standpoint of consumers' perceptions of Pick n Pay's food waste strategies, as well as an understanding of whether these practices are known by consumers and can help them minimise their own food waste. Finally, it is critical to determine whether consumers consider Pick n Pay to be meaningful in the context of their food waste strategies. Eight Pick n Pay customers were used in qualitative interviews. The main findings indicate that consumers are aware of some of the food waste strategies Pick n Pay has in place such as their reduced to clear strategy and the vacuum sealing of fresh meat. Consumers also believe that items purchased from Pick n Pay have a longer shelf life and Pick n Pay contributes significantly to the community. These findings indicate that consumers believe that Pick n Pay is doing enough to decrease food waste as well as assist their consumers. Based on these findings it is recommended that the Pick n Pay create awareness amongst consumers on how much more they are doing as a brand to decrease food waste as well as educate the public on how they can reduce food waste at home.
Keywords: Retail brands; Fast-moving consumer goods (FMCG); Consumer perception; Brand promise; Brand purpose